The Role of Bamboo Shoot Gigantochloa apus Extract in Decreasing MDA and Increasing IL-10 at The Atherosclerosis - Edy Soesanto; Edi Dharmana; Soeharyo Hadisaputro; Siti Fatimah Muis (Health Notions, 2019)
Introduction: Bamboo shoot Gigantochloa apus extract has antioxidant compounds that act as lipid peroxidation inhibitors and reduce free radical formation so that it can be used as an anti-inflammatory and anti-oxidative stress in the atherosclerosis. Aim: Knowing the effect of bamboo shoot Gigantochloa apus extract in reducing MDA levels and IL-10 increasing levels in rabbits given atherogenic diet. Methods: This experiment used randomized pre-test and post-test with control group design, in 24 New Zealand White rabbits divided into 4 groups randomly. MDA and IL-10 levels were examined by the ELISA method. Results and conclusion: Bamboo shoot Gigantochloa apus extract can reduce MDA levels and increase IL-10 levels significantly in accordance with increasing doses. The increase of MDA levels in the control group with all treatment groups was different (p = 0.0001), and between the treatment groups and other treatment groups there were also differences (p